Overcoming Vanitas, or Showing One’s Cards - Kubeckienė, Vaiva (Problemos, 2020)
In the article the painting Card Player Showing His Hand by T. Rombouts (17th c. Netherlands) is being interpreted. It is noticed that two existential manifestations may interact in this composition: the gambler’s and Vanitas. In the first part of this article, an analysis is made how Rombouts presents card play as a way of being and how he integrates it into the genre of Vanitas. In the second part the hypothesis, is it proven that the composition of the painting continues the theme of Vanitas and questions it at the same time.
Keywords: gamble; Vanitas; Theodor Rombouts; Arūnas Sverdiolas